Efficacy and safety of four-factor prothrombin complex concentrate fixed, weight-based dosing for reversal of warfarin anticoagulation. Issue 1 (1st January 2020) - Endres, Kaitlin; St. Bernard, Rosanne; Chin-Yee, Ian; Hsia, Cyrus; Lazo-Langner, Alejandro
ABSTRACT: Background: Four-factor prothrombin complex concentrate (4F-PCC) is widely used for urgent reversal of anticoagulation with warfarin, but the optimal 4F-PCC dosing approach is unknown. Herein, we sought to determine the efficacy of a novel fixed, weight-based dosing nomogram. Methods: We retrospectively studied consecutive adult patients receiving fixed, weight-based 4F-PCC dosing for warfarin reversal between 30 April 2009 and 31 December 2010. The primary outcome was reversal of warfarin anticoagulation, defined as INR ≤1.5 within 6 h. Secondary outcome was the occurrence of thromboembolic events. Results: A total of 227 patients (56% male), with a median age of 74 years and a median weight of 76kg were evaluated. The most common indications for 4F-PCC were active bleeding (37.4%: 12.7% intracranial, 12.3% gastrointestinal, 4.0% trauma, 8.4% other), reversal for a procedure (22.0%), reversal for surgery (29.5%) or other (11.1%). 66.1% of patients achieved an INR ≤1.5 within 6 h of 4F-PCC administration. 95.0% (57/60) of patients completed a planned procedure and 95.7% (67/70) of patients completed a planned surgery. The median baseline INR was 2.9 (1.5–10) and decreased significantly to a median of 1.3 (1.0–3.7) ( p < .001) post-4F-PCC administration. There was no statistically significant difference in response to a fixed, weight-based dose of 4F-PCC based on pre-PCC INR, as long as the pre-treatment INR was ≤ 4.5. Although the majority of patients in our study (99%) received doses over 1000IU, rates of thrombosis were low (1.8%). Conclusion: Fixed, weight-based dosing of 4F-PCC is effective for reversing warfarin anticoagulation in patients with a pre-dosing INR ≤ 4.5.